Colton's killer pursuit - Quinn, Tara Taylor (Harlequin romantic suspense, 2021)
"Everleigh Emerson just escaped wrongful conviction for murder. That doesn't mean she's safe. After Clarke Colton witnesses an attempt on her life, the PI convinces Everleigh to let him help her--even if it means pretending to be her boyfriend. Everleigh trusts that Clarke wants to catch the killer who's after her. But can she trust the attraction that's growing between her and her protector?" -- Page [4] cover.